CutPoints and Separations in Alpha- Connected Topological Spaces - Mahmoud, Balqees K.; Yousif, Yousif Y. (Iraqi Journal of Science, 2021)
This paper introduces cutpoints and separations in -connected topological spaces, which are constructed by using the union of vertices set and edges set for a connected graph, and studies the relationships between them. Furthermore, it generalizes some new concepts.